Effect of ultrasonication and use of aminopeptidase from Aeromonas proteolytica on quality parameters of fish protein hydrolysates from side streams of Atlantic mackerel (Scomber scombrus) - Cropotova, Janna; Kvangarsnes, Kristine; Stangeland, Janne; Le Gall, Amélie; Rustad, Turid (Frontiers in Nutrition, 2025)
In the present study, both ultrasonication (US) and enzymatic treatment with aminopeptidase from Aeromonas proteolytica (AAP) were applied as a post-treatment to fish protein hydrolysates (FPH) recovered from Atlantic mackerel. The single and combined effects of AAP and US treatments at 300 W and 500 W at 20 kHz for 10 min on the physicochemical characteristics of FPH were assessed. The results showed a significant decrease (p < 0.05) in soluble proteins after application of US treatment of FPH at 300 W and 500 W (79.1 and 70.3%, respectively) and US treatment at 300 W and 500 W together with AAP (50.3 and 72.5%, respectively) compared to control (84.4%). This is due to cavitation effect of sonication resulting in aggregation of peptides. This decrease was accompanied by a significant decrease in thiol groups in all experimental FPH samples varying from 5.85 to 9.54 nmol/mg compared to control (12.86 nmol/mg). At the same time, there was a significant increase in the distribution of small peptides with molecular weight (MW) between 200 and 1,000 Da along with a significant decrease in medium-size peptides with MW of 1,000 and 5,000 Da in all AAP-treated FPH samples compared to FPH without AAP. The proportion of essential amino acids increased significantly (p < 0.05) in all experimental FPH samples varying from 28.2 to 29.1% except for 500 W + AAP (24.2%) compared to control (25.7%), revealing a positive combined effect of AAP and US treatment on nutritional profile of mackerel hydrolysates. However, there was no significant difference in the proportion of hydrophobic free amino acids responsible for bitter taste between any of experimental FPH samples and control. Regarding color parameters, there was a significant increase in lightness accompanied by a significant decrease in redness in all US-treated FPH samples compared to control due to ultrasound-induced cavitation effect changing the secondary structure of peptide molecules. The novel approach of combined use of US and AAP to improving physicochemical parameters of mackerel FPH may provide valuable insights into process optimization for enhanced quality and functional properties of fish protein ingredients.